2024
DOI: 10.7150/thno.88759
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of MYC to mitigate chemoresistance in preclinical models of squamous cell carcinoma

Shuo Liu,
Zhen Qin,
Yaqing Mao
et al.

Abstract: Rationale: Cisplatin-based chemotherapy is the first-line treatment for late-stage head and neck squamous cell carcinoma (HNSCC). However, resistance to cisplatin has become a major obstacle for effective therapy. Cancer stem cells (CSCs) are critical for tumor initiation, growth, metastasis, and chemoresistance. How to effectively eliminate CSCs and overcome chemoresistance remains a key challenge. Herein, we confirmed that MYC plays critical roles in chemoresistance, and explored targeting MYC to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Drugadjuvant therapies such as chemotherapy and immunotherapy play a key role in the treatment of head and neck cancer, improving surgical outcomes and reducing recurrence risk. (Harrington et al, 2023;Liu et al, 2024a). However, drug resistance during treatment limits long-term efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drugadjuvant therapies such as chemotherapy and immunotherapy play a key role in the treatment of head and neck cancer, improving surgical outcomes and reducing recurrence risk. (Harrington et al, 2023;Liu et al, 2024a). However, drug resistance during treatment limits long-term efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…It has potential efficacy against drug-resistant head and neck cancer by inhibiting cancer cell proliferation and promoting apoptosis (Guo et al, 2019;Gao et al, 2020). In addition, artemisinin (Li, 2021) and its derivatives are complementary in traditional Chinese medicine (Roh et al, 2017). Studies have shown that they can regulate tumor cell signaling through multiple pathways and inhibit drug resistance in head and neck cancer.…”
Section: Introductionmentioning
confidence: 99%